Trends in Mobile Web Information Systems MobiWIS 2013 International Workshops, Paphos, Cyprus, August 26-28, 2013, Revised Selected Papers - Matera, Maristella; Rossi, Gustavo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the revised selected papers of the workshops of the 10th International Conference on Mobile Web Information, MobiWIS 2013, held in Paphos, Cyprus, in August 2013. The conference hosted two workshops: the First International Workshop on Future Internet of Things and Cloud, FICloud 2013, focusing on the Internet of Things and its relation with cloud computing and the Fourth International Workshop on Service Discovery and Composition in Ubiquitous and Pervasive Environments, SUPE 2013, addressing the issues that characterize automatic service composition in ubiquitous and pervasive computing. The 14 papers presented were carefully reviewed and selected from various submissions.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Management information systems; Computer Science; Information Systems and Communication Service; Business Information Systems; Software Engineering; Computer Communication Networks